2004
DOI: 10.4028/www.scientific.net/kem.264-268.985
|View full text |Cite
|
Sign up to set email alerts
|

Grain Growth in Corundum Oxides-Doped Uranium Dioxide and Effects of Grain Growth to the Mechanical Properties of Uranium Dioxide such as Elasticity Determined by Ultrasonic Methods

Abstract: In this study, ex-ADU UO 2 powders are doped by small amounts of various corundum oxides such as Cr 2 O 3 , Ti 2 O 3 , Al 2 O 3 , V 2 O 3 . Doped UO 2 powders were pressed up 50% theoritical density (TD) and sintered under 90% Ar + 10% H 2 atmospheres at 1700 ˚C for duration of 4 hours. Pellet densities, longitudinal and shear wave ultrasonic velocities for each pellet were measured. Average grain diameter for each pellet was found by image analysis system. Elastic properties of pellets were determined from ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Some evidence exists that Y 2 O 3 may also inhibit grain growth [6], while the studies with V 2 O 5 have shown varying results. [6,7,8,9] The solid solubility of the additive in UO 2 is a key aspect to its effect upon grain growth. [9] All additives in solid solution are believed to increase material transport rates.…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence exists that Y 2 O 3 may also inhibit grain growth [6], while the studies with V 2 O 5 have shown varying results. [6,7,8,9] The solid solubility of the additive in UO 2 is a key aspect to its effect upon grain growth. [9] All additives in solid solution are believed to increase material transport rates.…”
Section: Introductionmentioning
confidence: 99%